2020
DOI: 10.5812/modernc.106905
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Skills Training Versus Metacognitive Therapy: A Comparison of Effectiveness on Anxiety in Nurses Working in Intensive Care Units and Emergency Department

Abstract: Background: Anxiety is an outcome of a stressful work environment, like the clinical environment, which decreases the mental health level and delays the provision of services to patients. Objectives: This study examined the effects of resilience skills training and metacognitive therapy on nurses’ anxiety working in Intensive Care units (ICUs) and Emergency Department (ED). Methods: This randomized controlled field trial was carried out on 54 nurses working in ICU, PICU, NICU, and ED of Valiasr Hospital, Birja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…In a study by Han in Korea, a significant relationship was established among metacognition, shared leadership, and resilience [ 35 ]. This study was consistent with the results of Hasani's study [ 36 ] and the study of Yoosefi and Karimipoor [ 37 ]. In explaining these findings, it can be said that belief and awareness of individual abilities and inabilities, which are considered to be part of the characteristics of the metacognition system, strengthen motivation, and initiate a series of actions to win the task.…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Han in Korea, a significant relationship was established among metacognition, shared leadership, and resilience [ 35 ]. This study was consistent with the results of Hasani's study [ 36 ] and the study of Yoosefi and Karimipoor [ 37 ]. In explaining these findings, it can be said that belief and awareness of individual abilities and inabilities, which are considered to be part of the characteristics of the metacognition system, strengthen motivation, and initiate a series of actions to win the task.…”
Section: Discussionsupporting
confidence: 93%
“…The sample size was also estimated to be about 24 nurses in each group, according to the sample size formula, the mean and standard deviation (SD) reported in the previous study [ 9 ], with a 95% confidence interval, and a 80% test power. …”
Section: Methodsmentioning
confidence: 99%
“…Some researchers suggest that resilience skills training based on Nan Henderson’s Resiliency Training Program can reduce the job stress and anxiety of emergency and intensive care nurses. This program consisted of self‑confidence reinforcement, management of emotions and feelings, coping with stress, anger management, effective communication, problem‑solving, decision‑making, purposeful planning to achieve goals, and foresight [ 6 , 9 ]. Other study utilized mindfulness, gratitude, self-care, and social support to enhance the resilience of nurses and mitigate their stress and anxiety [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] (2013) on depression of female students and Hasani et al . [ 27 ] (2020) on the anxiety of nurses. There was no significant difference between the two groups in the first study, but in the second study, the resilience group showed better results.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference between the two groups in the first study, but in the second study, the resilience group showed better results. [ 26 27 ] Nevertheless, there is no research, as yet, to compare the effects of these two programs on the work stress of Iranian nurses. This study had two aims: (1) to examine whether resilience skills training and MCT can improve the job stress of nurses working in intensive care units and emergency departments and (2) to compare the effect of these two programs on the job stress of nurses.…”
Section: Introductionmentioning
confidence: 99%